Aerobics as a creative program in Physical Education at the institutions of higher education - Fučkar Reichel, K. (Array, 2008)
To make education and class interesting, creative and motivating for students demands a high criterion from a lecturer that needs to demonstrate knowledge and competence to fulfill the goals of physical education. One of the most popular elective kinesiological programs in physical education at the institutions of higher education is group aerobics. Specifically, Hi-Lo, New body and Step offer basic motoric knowledge and skills required to actively participate and enjoy all other types of aerobics. At the beginning of every semester students select one of available sport activities and that way form homogeneous groups based on specific interest. One of the most popular physical activities for female students is aerobics and that is in accord with findings of a number of previous studies. Motoric skills adapted in this area of physical education will assist in acquiring of positive habit of life-long recreational exercise. This study was conducted on a sample of 879 female students of the first year and it shows that they prefer sports related to music, rhythm and esthetics such as dance and aerobics. Characteristic of all aerobics programs, in essence multistructural cyclic activities, is a big number of relatively simple motions of various kinds that enables optimal conditions for functioning of respiratory and cardiovascular systems. Aerobics is equally efficient in achieving positive transformational effects of functional capabilities of organs and body as well as other endurance exercises. While exercising with equivalent intensity, frequency and duration, it is possible to achieve equivalent values of heartbeats per minute and oxygen intake as running on a treadmill or running/walking. Aerobics can boost confidence and reduce possible dissatisfaction with our own shape, which is important in adolescence. Music as essentially obligatory and constitutive component of dance program is great motivator and assists in reduction of manifested fatigue. Diversity of sports program enables students to find physical activities that are the most appropriate for their anthropological characteristics, motoric skills, and acquired habits for prolonged exercise and healthy life-style.